Preschool children's repeating patterning skills: evidence of their capability from a large scale, naturalistic, Australia wide study - Larkin, Kevin; Resnick, Ilyse; Lowrie, Thomas (Mathematical thinking and learning, 2024)
Patterns are a fundamental component of mathematics, and the patterning ability of young children has been well researched; however, this research has largely been conducted with relatively small cohorts (±70) and in an interventionist way (in laboratory settings or with researchers directly intervening in educational contexts). The current study examines the patterning skills of approximately 3 200 children in a naturalistic setting. As part of a larger, early years' STEM engagement program, children were provided patterning opportunities across one school term. The data presented here provides information regarding the children's performance on the tablet-based activities embedded in the program. Findings indicate that 3.5- to 4.5-year-old children were able to copy, extend, insert missing elements, fix, and create patterns, using a range of two, three or four elements pattern structures. These findings, from a large-scale naturalistic setting, confirm some aspects of the existing laboratory-based research, whilst also indicating that some children are more capable in terms of creating patterns than the existing research suggests. These findings have implications for educators when they are planning play-based patterning activities with preschool children.